Kebutuhan Mahasiswa terhadap Bahan Ajar di Era Pandemi - Lira Hayu Afdetis Mana (Ranah: Jurnal Kajian Bahasa, 2021)
Teaching materials are one of the important components needed in the learning process. With the appropriate teaching materials, it is hoped that it can help the smooth running of learning activities. Likewise with teaching materials in this Pandemic Era. Teaching materials that have been used in learning activities are simple teaching materials made by lecturers. This study aims to analyze student needs for teaching materials in the era of the COVID-19 pandemic, at STKIP PGRI West Sumatra. The subjects in this study were 106 students of STKIP PGRI West Sumatra. The data in this study were obtained from the results of a questionnaire on the analysis of student needs for teaching materials in the Covid 19 pandemic era through the google form that has been provided by researchers to find out student responses regarding the teaching materials that have been obtained so far. The results of the research from the analysis of student needs for teaching materials are: first, students need teaching materials provided by lecturers from e-learning. Second, students understand a teaching material more quickly if the teaching material is provided by the lecturer through e-learning then download and print it. third, students prefer a power point display that is complete with lecturers' explanations. fourth, students like the use of a standard language style, but not rigid of a teaching material. Fifth, the teaching materials that have been given by lecturers during online chasing are sufficient to meet the needs but not maximally, sixth, the teaching materials provided by lecturers during online learning are quite relevant / in accordance with the topic, seventh, the need for students for teaching materials is very high. This shows that students need more detailed information about the lesson in order to gain a deep understanding. AbstrakPenelitian ini bertujuan untuk menganalisis kebutuhan mahasiswa terhadap bahan ajar di era pandemi covid 19. Subjek dalam penelitian ini adalah mahasiswa STKIP PGRI Sumbar yang. Data pada penelitian ini diperoleh dari hasil angket analisis kebutuhan mahasiswa terhadap bahan ajar di era pandemi covid 19 melalui google form yang telah disediakan peneliti untuk mengetahui tanggapan-tanggapan mahasiswa mengenai bahan ajar yang diperoleh selama ini. Hasil penelitian dari analisis kebutuhan mahasiswa terhadap bahan ajar yaitu: pertama, mahasiswa membutuhkan bahan ajar yang disediakan oleh dosen dari e-learning. kedua, mahasiswa lebih cepat memahami sebuah bahan ajar jika bahan ajar tersebut diberikan oleh dosen melalui e-learning lalu mengunduh dan memprintnya. ketiga, mahasiswa lebih menyukai tampilan power point yang lengkap disertai penjelasan dosen, keempat, mahasiswa menyukai penggunaan gaya bahasa baku, namun tidak kaku dari sebuah bahan ajar. kelima,  bahan ajar yang diberikan dosen saat pembelajaran daring selama ini cukup memenuhi kebutuhan namun belum maksimal, keenam, bahan ajar yang diberikan dosen saat pembelajaran daring cukup relevan/sesuai dengan topik, ketujuh, kebutuhan mahasiswa terhadap bahan ajar sangat tinggi. Ini menunjukkan bahwa mahasiswa membutuhkan informasi yang lebih detail tentang pelajaran  dalam rangka mendapatkan pemahaman yang mendalam.